Dystonia Different Prospects - Mohamed Gaber Rizk, Tamer (IntechOpen, 2018)
The book contains four chapters discussing dystonia from a new perspective. Dystonia may result from either diffuse or localized pathology of the cerebral cortex, brain stem, or spinal cord. Management of dystonia is challenging, and specific goals should be identified. Dystonia is considered one of the most disabling conditions in the pediatric age group, which may remain until adulthood; treatment is usually unsatisfactory. Meige's syndrome, or "oromandibular dystonia," may be misdiagnosed as temporomandibular joint or psychogenic disorder, which will alter management and delay proper treatment. Dystonia with non-motor disorders includes sleep, cognitive, pain, sensory, and psychiatric disorders, and their pathophysiological and biochemical mechanisms and specific treatment are discussed. This book will be of interest to GPs, neurologists, family physicians, and internal medicine specialists.